One Method for the Systematic Evaluation of Adverse Drug Experience Data within a Pharmaceutical Firm - Westlin, W. F.; Cuddihy, R. V.; BursiK, R. J.; Seifert, Beverley G.; Koelle, Joyce G. (Methods of Information in Medicine, 1977)
Post-marketing surveillance of drug adverse experience incidents constitutes a major interest for physicians, pharmaceutical firms and federal regulatory bodies alike. The development and operation of a total information system for the management of adverse experience data related to a single pharmaceutical firm’s commercial products is described. Data is carefully collected from clinical investigations, visits and correspondence with practicing physicians and from the published medical literature. Each such alleged incident is carefully medically reviewed. Thereafter, the data is reported to the United States Food and Drug Administration (FDA) and entered into an internal data bank. Computer management of the data for information retrieval and trend analysis was accomplished in a rapid and economical fashion by the use of commercially available computer programming packages. This approach, combining meticulous data collection, computer management of files and links to the firm’s FDA reporting system offers a flexible, thorough approach operative within the economic constraints naturally inherent within a single corporation.
Keywords: Drug Adverse Effects; Information Retrieval System; Food and Drug Administration Reporting; Trend Analysis